Cloning and expression of the lectin gene from the mushroom Agrocybe aegerita and the activities of recombinant lectin in the resistance of shrimp white spot syndrome virus infection. (January 2019) - Chang, Yun-Shiang; Chen, Jian-Nan; Chang, Kun-Hung; Chang, Yi-Ming; Lai, Ying-Jang; Liu, Wang-Jing
Abstract: Lectin is a protein with multiple functions. In this study, the full-length cDNA of the Agrocybe aegerita lectin (AAL) gene was cloned, recombinant AAL (AAL-His) was expressed, and the activities of AAL-His were analyzed. Northern blot analysis showed that the major AAL transcript is approximately 900 bp. Sequence analysis showed that the coding region of AAL is 489 bp with a transcription start site located 39 nucleotides upstream of the translation initiation codon. In an agglutination test, AAL-His agglutinated rabbit erythrocytes at 12.5 μg/ml. AAL-His also showed antiviral activity in protecting shrimp from white spot syndrome virus (WSSV) infection. This anti-WSSV effect might be due to the binding of AAL-His on WSSV virions via the direct interactions with four WSSV structural proteins, VP39B, VP41B, VP53A and VP216. AAL demonstrates the potential for development as an anti-WSSV agent for shrimp culture. It also implies that these four AAL interaction WSSV proteins may play important roles in virus infection. Highlights: Full length cDNA of Agrocybe aegerita lectin (AAL) gene was cloned. Recombinant AAL (AAL-His) showed with anti- white spot syndrome virus (WSSV) activity. The anti-WSSV effect of AAL-His might through to its binding on WSSV virions. AAL-His could interact with WSSV structural proteins, VP39B, VP41B, VP53A and VP216.